Pengaruh Citra Merek dan Inovasi Produk Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Mediasi Pada Produk Indomie di Kartasura - Silvia Putri; Fani Anisa; Rayhan Gunaningrat (Institut Nalanda, 2024)
In the current era of rapid progress, the development of various types of business continues to develop and becomes increasingly competitive. This encourages companies to always strive to increase market share and attract consumer attention. The aim of this research is to understand the impact of brand image and product innovation on customer loyalty, with customer satisfaction as a mediating variable, especially for Indomie consumers in Surakarta. There were 100 participants in this research and data was collected through an online survey using a Google form. The sampling technique was carried out using purposive sampling techniques and primary data types, as well as collecting questionnaires. The results of the analysis show that customer satisfaction acts as a mediator in the relationship between brand image and product innovation on customer loyalty, with a partial influence